Keratorefractive Effect of High Intensity Focused Ultrasound Keratoplasty on Rabbit Eyes - Zhiyu Du; Pisong Yan; Qiang Luo; Dan Zhang; Yu Zhang (Journal of Ophthalmology)
Purpose. To evaluate high intensity focused ultrasound (HIFU) as an innovation and noninvasive technique to correct presbyopia by altering corneal curvature in the rabbit eye. Methods. Eighteen enucleated rabbit eyes were treated with a prototype HIFU keratoplasty. According to the therapy power, these eyes were divided three groups: group 1 (1 W), group 2 (2 W), and group 3 (3 W). The change in corneal power was quantified by a Sirius Scheimpflug camera. Light microscopy (LM) and transmission electron microscopy (TEM) were performed to determine the effect on the corneal stroma. Results. In the treated eyes, the corneal curvature increases from 49.42 ± 0.30 diopters (D) and 48.00 ± 1.95 D before procedure to 51.37 ± 1.11 D and 57.00 ± 1.84 D after HIFU keratoplasty application in groups 1 and 3, respectively. The major axis and minor axis of the focal region got longer when the powers of the HIFU got increased; the difference was statistically significant (p<0.05). LM and TEM showed HIFU-induced shrinkage of corneal stromal collagen with little disturbance to the underlying epithelium. Conclusions. We have preliminarily exploited HIFU to establish a new technique for correcting presbyopia. HIFU keratoplasty will be a good application prospect for treating presbyopia.